Jan Schoonhoven - Camp, D'Laine; Richards, Lynne (Nai010 publishers, 2015)
Jan Schoonhoven (1914-1994) became world-famous with his sculptural reliefs and works on paper. For nearly 40 years, Schoonhoven worked on developing his reliefs (made of papier-mâché, paper and cardboard) alongside his job as a civil servant at the Dutch Post Office. For the first time, this monograph places Jan Schoonhoven in an international context, as an active and influential player in the European post-war developments in art. The early years are covered in detail: the influences of, for example, Paul Klee and Jackson Pollock, and his participation in the Nederlandse Informele Groep during the late 1950s. Schoonhovens involvement in the Dutch Nul group and the international ZERO movement is also highlighted. Likewise, the monograph shows how Schoonhovens oeuvre continued to develop, even in the years after Nul. This monograph, featuring many hitherto unknown works and photographs, sheds new light on the work and life of this twentieth-century master of white Exhibition: Stedelijk Museum Schiedam, The Netherlands (31.10.2015-14.02.2016)
Ausstellungsdaten ermittelt
Keywords: Schoonhoven, Jan / (Johannes Jacobus) / 1914-1994; Schoonhoven, Jan J. -- 1914-1994; Ausstellungskatalog -- Stedelijk Museum -- 31.10.2015-14.02.2016 -- Schiedam; Bildband